Recurrent diabetic ketoacidosis and a brief history of brittle diabetes research: contemporary and past evidence in diabetic ketoacidosis research including mortality, mental health and prevention. Issue 11 (29th August 2019) - Garrett, C. J.; Choudhary, P.; Amiel, S. A.; Fonagy, P.; Ismail, K.
What's new?: Diabetic ketoacidosis continues to be a common cause of admission in Type 1 diabetes and is the leading cause of mortality in young people with Type 1 diabetes. Diabetic ketoacidosis suggests all‐cause mortality over 15% at 5‐year follow‐up. This review brings together the limited current evidence in diabetic ketoacidosis prevention and links it with the mental health literature of diabetic ketoacidosis and the historical literature of brittle diabetes, a significant component of which comprised people with recurrent diabetic ketoacidosis. From a clinical perspective, more caution is required in the assessment and management of people with recurrent diabetic ketoacidosis given the potential for a treatable mental health condition and substantial risk of early mortality. Abstract: Pharmacological, technological and educational approaches have advanced the treatment of Type 1 diabetes in the last four decades and yet diabetic ketoacidosis (DKA) continues to be a leading cause of admission in Type 1 diabetes. This article begins by reviewing the contemporary epidemiological evidence in DKA. It highlights a rise in DKA episodes in the last two decades, with DKA continuing to be the leading cause of death in young people with Type 1 diabetes, and that DKA episodes are a marker for subsequent all‐cause mortality. It also summarizes the limited evidence base for DKA prevention and associations with psychopathology. To emphasize the importance of this group with high‐risk Type 1 diabetes and the degree to which they have been overlooked in the past two decades, the article summarizes the research literature of recurrent DKA during 1976–1991 when it was extensively investigated as part of the phenomenon of 'brittle diabetes'. This period saw numerous basic science studies investigating the pathophysiology of recurrent DKA. Subsequently, research centres published their experiences of brittle diabetes research participants manipulating their treatment under research conditions. Unfortunately, the driver for this behaviour and whether it was indicative of other people with ketoacidosis was not pursued. In summary, we suggest there has been a stasis in the approach to recurrent DKA prevention, which is likely linked to historical cases of mass sabotage of brittle diabetes research. Further investigation is required to clarify possible psychological characteristics that increase the risk of DKA and thereby targets for DKA prevention.